Giacomo Verde. Attraversamenti tra teatro e video (1992-1986) - Monteverdi, Anna Maria (Milano University Press, 2022)
A little more than a year after the death of Giacomo Verde, pioneer of video/interactive art, techno-theatre and Italian "artivist", the corpus of unpublished drawings and sketches in pencil, pastel and collage for videos, video installations and video performances by the artist from the period 1986-1992 is published. This is the first publication  from the Giacomo Verde Archive and it illustrates Verde's first "techno-artistic" phase: a well-documented and creatively rich period, when in 1983 he arrived, self-taught, from popular and street theatre to video art, works and installations whose characteristic feature was the craftsmanship of the "technological artefact", the use of low technology and the addition of poor materials. The authors  Anna Maria Monteverdi Dalila Flavia D'Amico, Vincenzo Sansone, dedicate the book to the warm memory of the unforgettable Giacomo Verde.